Amanda Witmer, Jesus, the Galilean Exorcist. His Exorcisms in Social and Political Context (Library of New Testament Studies. Library of the Historical Jesus Studies 10; London: T&T Clark International, 2012) - Wróbel, Mirosław S. (The Biblical Annals, 2015)
Book review: Amanda Witmer, Jesus, the Galilean Exorcist. His Exorcisms in Social and Political Context (Library of New Testament Studies. Library of the Historical Jesus Studies 10; London: T&T Clark International, 2012). Pp. 247. $ 120. ISBN 978-0-567-57552-4.